Poverty, bioethics and research (Revista Latino-Americana de Enfermagem, 2007)
The article presents a reflection on conception of poverty as a condition or circumstance that restricts personal autonomy and increases vulnerability. Focusing on bioethical arguments, the authors discuss two perspectives: (i) economic, that relates poverty to incapacity to work and (ii) ethical-philosophical, which relates poverty to inequality and injustice. The first perspective corresponds to the World Bank's view according to its recommendations to the political and economic adjustment in Latin America. The second one is based on concepts of fairness and equality as components of social justice. The subjects' autonomy and vulnerability have been under question in an international movement that requests revision of ethical guidelines for the biomedical research. The bioethical arguments presented in this article enhance a discussion on unfair treatment to subjects enlisted in protocols sponsored by rich countries and hosted by poor nations.